Softness presentation by combining electro-tactile stimulation and force feedback - Suga, Yui; Takeuchi, Masahiro; Tanaka, Satoshi; Kajimoto, Hiroyuki (Frontiers in Virtual Reality, 2023)
To provide realistic tactile sensations in a virtual environment, it is necessary to stimulate both the cutaneous and proprioceptive senses. This study focuses on a realistic method of presenting softness through the use of electro-tactile stimulation. Our system combines a force-feedback device with an electric stimulator to create a soft sensation by applying a reaction force and spreading cutaneous sensation based on the amount of indentation. We measured the change in the contact area of gel samples and used electric stimulation to reproduce the increase in the contact area of the sample. We conducted a psychophysical experiment to evaluate the effectiveness of the combination of cutaneous and force sensations and confirmed that the sensation of softness was enhanced by the simultaneous presentation.